2009
DOI: 10.1021/ja9066628
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of RNA Enzyme Activity in the Molecular Crowding Media of Cosolutes

Abstract: Short RNA sequences exhibiting the activity of a target RNA cleavage are promising for cellular gene regulation and biosensor research, but the reaction media different from an aqueous solution may cause unanticipated molecular interactions and properties. In this study, we investigated the molecular crowding effects arising from steric crowding and altered solvent properties on the hammerhead ribozyme activity using water-soluble neutral cosolutes. Poly(ethylene glycol) (PEG) and other cosolutes at 20 wt % in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 62 publications
8
142
0
Order By: Relevance
“…The hammerhead ribozyme, ligase ribozyme, and substrate RNAs having a 5 -triphosphate group were prepared by in vitro transcription using T7 RNA polymerase and purified by polyacrylamide gel electrophoresis, as described previously [34]. Other RNAs, DNAs, and a DNA-RNA chimeric strand, purified by high performance liquid chromatography, were purchased from Hokkaido System Science (Sapporo, Japan) or Fasmac (Atsugi, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The hammerhead ribozyme, ligase ribozyme, and substrate RNAs having a 5 -triphosphate group were prepared by in vitro transcription using T7 RNA polymerase and purified by polyacrylamide gel electrophoresis, as described previously [34]. Other RNAs, DNAs, and a DNA-RNA chimeric strand, purified by high performance liquid chromatography, were purchased from Hokkaido System Science (Sapporo, Japan) or Fasmac (Atsugi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…A simple interpretation of this correlation is that the transition state is electrostatically stabilized in less-polar media. However, our previous study identified an apparent increase in Mg 2+ -binding affinity to HH(S) in mixed solutions with a low dielectric constant [34,35]. The substrate cleavage catalyzed by the hammerhead ribozyme requires the involvement of several Mg 2+ ions, and at least one Mg 2+ ion binds to the site with highly negative electrostatic potential located near the scissile phosphate of the substrate [49].…”
Section: Effects On the Hammerhead Ribozymementioning
confidence: 97%
See 2 more Smart Citations
“…investigated the stability and catalytic activity of a minimal hammerhead ribozyme with PEG8000 as co-solute [333,334]. The authors find that large neutral co-solutes stabilize the tertiary structure and enhance catalytic rates especially at low Mg 2+ concentrations.…”
Section: Effects Of Solvent Permittivity and Co-solutes To Mimic Macrmentioning
confidence: 99%